MANAGERIAL DECISION-MAKING IN UNCERTAIN ECONOMIC ENVIRONMENTS: A BEHAVIORAL TAX COMPLIANCE APPROACH - Loso Judijanto; Ingrid Panjaitan; Baskoro Ajie (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Economic uncertainty driven by global crises, regulatory changes, and market volatility has intensified the complexity of managerial decision-making, particularly in relation to tax compliance behavior. This study aims to examine how managers make tax-related decisions in uncertain economic environments by adopting a behavioral tax compliance perspective. Using a literature review methodology, this research systematically analyzes and synthesizes findings from prior empirical and theoretical studies in the fields of behavioral economics, taxation, and managerial decision-making. The review highlights that managerial tax compliance is not solely determined by economic rationality, but is significantly influenced by behavioral factors such as risk perception, moral norms, trust in tax authorities, cognitive biases, and social influences. Furthermore, uncertainty amplifies the role of heuristics and subjective judgment, leading managers to balance compliance considerations with survival strategies and organizational performance objectives. The findings suggest that behavioral dimensions play a critical role in shaping tax compliance decisions under uncertainty, challenging traditional deterrence-based tax models. This study contributes to the literature by integrating managerial decision-making theory with behavioral tax compliance, offering a more comprehensive framework for understanding tax behavior in uncertain economic contexts. The results also provide practical implications for policymakers in designing adaptive and behaviorally informed tax regulations that encourage voluntary compliance during periods of economic instability.